Periodic cellular automata of Period-3 - Ganikhodjaev, Nasir; Asimoni, Raihan (2015)
Cellular automata are a new approach that has been rapidly used in many area of science. In this paper, we introduce a notion of periodic one-dimensional cellular automata. In addition, we calculate entropy of some periodic cellular automata of period-3 and present the simulation for some fractal type periodic cellular automata.